Challenges in Access to New Therapeutic Agents: Marginalized Patients With Cancer in Pakistan and the Need for New Guidelines. (17th February 2022) - Aziz, Zeba; Naseer, Hafsa; Altaf, Anjum
Abstract : PURPOSE: Cancer care disparities persist among the medically underserved patients with cancer in Pakistan. To determine the access that marginalized patients with cancer have to chemotherapy and newer targeted agents in Pakistan approved by essential medicine list 2017, the barriers that patients face in getting such access, the implications of the barriers for the effectiveness of treatment, and ways of overcoming those barriers, with particular attention to breast cancer (BC), diffuse large B-cell lymphoma (DLBCL), and chronic myeloid leukemia (CML), need to be addressed. METHODS: A cross-sectional survey of 28 private and public cancer centers targeting more than 50% of patients with cancer for year 2018 was conducted with focus on access to optimal therapy for BC, DLBCL, and CML. To assess the impact of socioeconomic status on the effectiveness of treatment, patients were categorized into three main income groups—low, middle, and high according to gross domestic product per capita on the basis of which some patients were categorized as economically marginalized. Differences in quality of care in public and private sector hospitals were assessed by optimal delivery and completion of chemotherapy on the basis of international guidelines. Access to optimal dose and timings of targeted therapies were determined. RESULTS: In our marginalized patients, 30%-40% received optimal basic chemotherapy for BC and DLBCL. Less than 10% of patients with human epidermal growth factor receptor 2–positive BC completed 17 cycles of trastuzumab within 12 months. For DLBCL, hardly any patients received concurrent rituximab with chemotherapy for six cycles. Dose delays, modifications, and abandonment of treatment occurred in approximately 50% of the marginalized patients. In patients with CML, the compliance to imatinib/nilotinib was 85%. CONCLUSION: Significant barriers exist in providing optimal basic and targeted therapies to our indigent patients despite government funding and availability of access programs. Abstract :